2018
DOI: 10.1097/rlu.0000000000002152
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Brain in a Patient With Fatal Familial Insomnia

Abstract: A 57-year-old woman presented with a 3-month history of cognitive impairment, daytime somnolence, and violent sleep behavior. Her first- and second-degree relatives had similar symptoms prior to their premature deaths. Her MRI scan of the brain showed no significant abnormality. Electroencephalogram showed loss of slow-wave activity. Functional brain imaging performed with F-FDG PET was fused with her MRI scans. This demonstrated profound hypometabolism in bilateral thalami and the posterior cingulate cortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The thalamus changes detected in our study were also found in previous research. Previous FDG-PET studies reported hypometabolism in the bilateral thalamus, cingulum, cortices, and basal ganglia,( Khan and Bollu, 2020 , Provini, 2013 , Zhang et al, 2010 ) which is in line with our results ( Cortelli et al, 1997 , Provini, 2013 , Rupprecht et al, 2013 , Tham et al, 2018 ). As for thalamic subnuclei, current neuroimaging analysis remains scarce, whereas postmortem analyses have indicated medial dorsal and anterior ventral nuclei involvement, followed by involvement of the pulvinar and inferior olives,( Haïk et al, 2008 , Khan and Bollu, 2020 , Llorens et al, 2017 ) which supports our ROI analysis results.…”
Section: Discussionsupporting
confidence: 93%
“…The thalamus changes detected in our study were also found in previous research. Previous FDG-PET studies reported hypometabolism in the bilateral thalamus, cingulum, cortices, and basal ganglia,( Khan and Bollu, 2020 , Provini, 2013 , Zhang et al, 2010 ) which is in line with our results ( Cortelli et al, 1997 , Provini, 2013 , Rupprecht et al, 2013 , Tham et al, 2018 ). As for thalamic subnuclei, current neuroimaging analysis remains scarce, whereas postmortem analyses have indicated medial dorsal and anterior ventral nuclei involvement, followed by involvement of the pulvinar and inferior olives,( Haïk et al, 2008 , Khan and Bollu, 2020 , Llorens et al, 2017 ) which supports our ROI analysis results.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the reduction of the sleep spindles and K complexes indicates a decline in thalamic function [18]. Furthermore, 18-fluoro-deoxy-glucose-PET/CT detected prominent hypometabolism in bilateral thalami, which were consistently reported in previous publications [4,19]. Early pathological changes of FFI may be predominantly limited to the thalamus and adjacent areas.…”
Section: Discussionsupporting
confidence: 56%
“…Research, Society and Development, v. 10, n. 14, e168101421719, 2021 (CC BY 4.0) (Lee et al, 2014;Lima et al, 2020;Tham et al, 2018;Pedroso et al, 2013)…”
Section: Resultsmentioning
confidence: 99%